HUKUN KELUARGA KONTEMPORER DALAM TATA HUKUM YORDANIA DAN YAMAN SELATAN - Fauzan Al As’ari; Siah Khosyi’ah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the development of family law in Tunisia and Libya, focusing on the changes and influences of the legal systems implemented after independence. Tunisia, which gained its independence in 1956, underwent major transformations in family law with the enactment of the Personal Status Code, which adopted principles of secularism and modern thought. The reforms included the prohibition of polygamy, changes in the legal age for marriage, and the enforcement of women's rights in marriage and divorce. Meanwhile, Libya has a different legal history, shaped by the influence of Islam and Italian colonialism. After gaining independence in 1951, Libya retained an Islamic-based legal system, influenced by the Maliki school of thought and remnants of colonial legal rules. This study shows that although both countries share strong Islamic roots, the family law policies implemented differ significantly due to the political and social factors unique to each country.